Technology Readiness and Acceptance Model (TRAM) Pada Pengguna Rekam Medis Elektronik - Andriani, Rika; Pertiwi, Julia; Nisaa, Arifatun (Politeknik Negeri Jember, 2024)
The highest proportion of electronic medical records (EMR) implementation in Indonesia is level 3. It is just used for administration. EMR can improve patient care management. EMR is used to record patient services at RSJD Dr. Arif Zainudin Surakarta. An evaluation was never carried out to assess the EMR system. Technology readiness and user acceptance are important for developing an effective and efficient EMR. This study aimed to analyze the interaction of technology readiness and user acceptance of EMR based on the Technology Readiness and Acceptance Model (TRAM). This was an analitic-quantitative research with a cross-sectional design study. Data from EMR users was collected with a structured questionnaire. Data was analyzed using descriptive statistical analysis and SEM-PLS. The finding showed that technology readiness has significant positive effects on perceived ease of use, perceived usefulness, and use intention; perceived ease of use has significant positive effects on perceived usefulness. Perceived ease of use and perceived usefulness do not have significant effects on use intention. To improve EMR acceptance, it is necessary to develop easier and more practical features.